Faktor-Faktor Yang Mempengaruhi Kesediaan Wus Dalam Melakukan Deteksi Dini Kanker Serviks Di Puskesmas Manahan Surakarta - Lestari, Indah Siti; , Yuli Kusumawati, SKM., M.Kes (Epid); , Kusuma Estu Werdani, SKM., M.Kes (2016)
Cervical cancer is the second most lethal disease occuring in women. A total of 529,800 cervical cancer cases occur in the world in 2008 and 85% of which happens in developing countries. The number of cervical cancer sufferes in Surakarta in 2012 were 59, while in 2014 there were 313 cervical cancer sufferes registered in public health center in Surakarta and here were 2000 cervical cancer sufferes registered in hospital in Surakarta. Manahan public health center had the highest cervical cancer issue in 2014 as it had 56 sufferers. High risk of cervical cancer in women triggers them to perform early detection. This study aims at investigating factors determining the willingness of fertile women in performing early detection of cervical cancer at Manahan Public Health Center of Surakarta. This research applied observational design with cross-sectional approach. A total of 719 fertile women at Manahan Public Health Center of Surakarta were the research populations. Samples consisting of 236 people were selected using simple random sampling. Samples were analyzed statistically using chi square. The research results indicate significant relationship between knowledge (p=0,025), access of information (p=0,042), husband's support (p=0,010), and cadre's support (p=0,009) with willingness of fertile women in performing early detection of cervical cancer and